الاتصال الدعوي في القرآن الكريم دراسة تطبيقية حول أولي العزم من الرسل - بن سعيدي, سهام (Universty of Eloued جامعة الشهيد حمه لخضر, 2021)
الملخص: نظرا لأهميّة الاتّصال في العمليّة الدعويّة، تناولت هذه الأطروحة موضوع الاتصال الدعوي في القرآن الكريم دراسة تطبيقية حول أولي العزم من الرسل عليهم السلام، ابتداء بنوح عليه السلام إلى خاتم النبيين محمد صلى الله عليه وسلم وهم حسب الترتيب الزمني الذي أشارت إليه كتب السيرة والتاريخ: نوح- إبراهيم –موسى-عيسى –محمد عليهم السلام ، فقد مارسوا الاتصال الدعوي بشتى أساليبه ومضامين رسائله فكانت ممارسة فعالة ومتميزة تحملوا على إثرها أعباء الدعوة إلى الله، فجاءت هذه الدّراسة لجملة من الأهداف كان أهمها تبيان أهميّة الاتّصال بشتّى أنواعه ومستوياته في نشر الدّعوة إلى الله وكذا تفعيل دور القائمين عليه وتمكين الدّعاة من استغلاله بشكل أمثل من خلال الجمع بين متغيرين هما: الاتصال الدعوي المعاصر والاتصال الدعوي الذي نهجه أولي العزم من الرسل ، لتعالج واقع الاتّصال الدّعوي المعاصر وتفعيله ومن ثم النّهوض به. ولتحقيق أهداف الدّراسة تمّ الاعتماد على المنهج التحليلي لماهية الاتّصال، مرورا بأهمّ نماذجه وأركانه ووظائفه في القرآن الكريم بالرّجوع إلى دعوة أولو العزم من الرّسل، لتشكل ما يعرف بالاتّصال الدّعوي من خلال ما احتواه القرآن الكريم، محاولة منا لاستقراء النصوص التي وردت فيها قصص أولي العزم من الرسل عليهم السلام، وفي هذا الإطار كانت أهميّة دراسة علم الاتّصال الدّعوي كمنهج في ضوء مضامين القرآن الكريم. وتمحورت إشكالية الأطروحة حول كيفية تجلي العملية الاتصالية في دعوة أولي العزم من الرسل عليهم السلام، وفيما تمثلت أهم الأساليب التي انتهجها كل نبي لتبليغ رسالته لقومه، وما مدى تنوع المضامين الرسالية في دعوة كل نبي على حده وماهي نقاط التشابه بينهم، كما حاولنا معرفة موانع الاستجابة في دعوات الأنبياء نوح وإبراهيم وموسى وعيسى عليهم السلام مقارنة بدعوة محمد صلى الله عليه وسلم وكذا دور وتأثير خصائص المتلقي في دعواتهم على تحقيق الاستجابة. وللإجابة على تساؤلات الدراسة قمنا بتقسيمها إلى فصل تمهيدي كمدخل للدراسة ألقينا من خلاله الضوء على أهم المفاهيم والمصطلحات وكذا التعريف بأولي العزم وموارد ذكرهم في القرآن الكريم، أما الفصل الأول حاولنا من خلاله التطرق إلى الأسس التي يقوم عليها الاتصال وأهم مكوناته وخصائصه وكذا نماذجه و أهم الوظائف المنوطة به ، أما الفصلين الثاني والثالث كانا تطبيقا لأهم ما ورد من أسس الاتصال في الفصل الأول ومحاولة إسقاطها على دعوة أولي العزم من الرسل عليهم السلام اعتمادا على النص القرآني بالاستعانة بأهم التفاسير للخروج في نهاية كل مبحث بجملة من النتائج كان من أهمها: عمل أولو العزم من الرسل عليهم السلام على الاستراتيجيات والأساليب الاتصالية المعاصرة ، عدم الاستجابة للرّسالة لا يعني فشل القائم بالاتّصال على توصيل رسالته، لأنّ تحقيق الهداية بيد الله وهو المصدر المطلق لهذه الرّسالة. Résumé : فرنسية أو انجلزية Given the importance of connection in the process of Da’wah, this thesis has taken up the topic of connection in Da’wah in the holy Quran as an empirical study concerning the possessors of constancy of the prophets, peace be upon them. Therefore, there had to be an attempt to unveil the shortcomings of the Da’is in relation to the usage of the skills, techniques and methods of effective connection, through following the footsteps of The processors of constancy of the prophets ,peace be upon them, starting from Noah, peace be upon him, to the final of messengers Mohammed, peace be upon him, in accordance to the chronological order provided by the books of Seerah and history: Noah, Abraham, Moses, Jesus, Mohammed, peace be upon them all, for they had practiced the connection in Da’wah by its multiple forms and contents of its messages. Thus, the practice, upon which they bore the burdens of the Da’wah to Allah (SWT), was both effective and distinct. Accordingly, this message came to fulfil a collection of goals, most substantial of which was clarifying the importance of connection in all its forms and levels in spreading the Da’wah to Allah (SWT) as well as activating the role of those in charge and enabling the Da’is to take full advantage of this role in the best of ways through combining the two following variables: The modern Da’wah connection and the Da’wah connection approach created by the possessors of constancy of the prophets, to deal with the reality of the modern Da’wah connection, activate then promote it. In order to achieve the goals of the message, the descriptive analytical method was adopted to understand the meaning of connection by going through its most important models, pillars and functions in the holy Quran in reference to the Da’wah of the possessors of constancy of the prophets to form what is known as the Da’wah connection through the contents of the holy Quran, in an attempt to extrapolate the texts in which the stories of the possessors of constancy of the prophets occur. This frame encapsulates the importance of studying the science of The Da’wah connection as an approach in light of the contents of the holy Quran. The problem of this thesis revolves around: How the possessors of constancy of the prophets applied the process of The Da’wah connection, what are the most important methods followed by each prophet to relay his massage to his people, what is the range of diversity of the contents of the message in the Da’wah of each prophet and what are the points of similarities between them. We also attempted to know the obstacles which prevented a response in the stories of Noah, Abraham, Moses and Jesus in comparison to the Da’wah of Mohammed, peace be upon him, as well as the role and influence of the characteristics of the receiver of the Da’wah in relation to the achievement of a response. To answer the questions of this study, we have divided it into; an opening chapter, as an entry to the study through which we shed light on the most important concepts and vocabulary as well as the definitions of the possessors of constancy and the sources in which they are mentioned in the holy Quran. As for the first chapter, we attempted through it to get into the foundations upon which connection is based and it’s most important components, properties as well as its forms and the most vital functions assigned to it. As for the second and third chapters, they were an application of the most important of the foundations of connection to have been stated in the first chapter, as well as an attempt to project them onto the Da’wah of the possessors of constancy of the prophets, peace be upon them, depending on the Quranic text as well as the most important Tafasir in order to reach by the end of each theme a collection of results, most important of which are: the possessors of constancy of the prophets worked on the modern strategies and methods of connection, the absence of a response to the message does not mean the failure of the messenger in conveying the message, because the achievement of Hidaya is in the hands of Allah for he is the ultimate source for this message.
أطروحة دكتوراه تخصص دعوة و ثقافة إسلامية في العلوم الاسلامية
Keywords: الاتّصال-الدّعوة-القرآن – أولو العزم من الرّسل; Connection, Da’wah, Quran, The possessors of constancy of the prophets